The CPLANE protein Intu protects kidneys from ischemia-reperfusion injury by targeting STAT1 for degradation - Shixuan Wang (Nature Portfolio, 2018)
Intu is a planar cell polarity protein known to regulate ciliogenesis during embryonic development. Here, Wang et al. identify a role for Intu in adult kidneys, where they find it promotes degradation of STAT1 and thus prevents cilia loss and cell death upon ischemia-reperfusion injury.